Variation of life‐history parameters of Planococcus ficus (Hemiptera: Pseudococcidae) in response to grapevine nitrogen fertilization. (8th December 2014) - Cocco, A.; Marras, P. M.; Muscas, E.; Mura, A.; Lentini, A.
Abstract The effects of different nitrogen fertilization regimes on body size and selected life‐history parameters (development time, survival, fecundity and fertility) of the vine mealybug, Planococcus ficus (Signoret) (Hemiptera: Pseudococcidae), were investigated on potted grapevines under laboratory and screenhouse conditions. In both trials, five groups of four grapevines each were supplied with 0, 0.25, 0.5, 1.0 or 2.0 g/l of ammonium nitrate fertilizer for a month and then artificially infested with 200 first‐instar vine mealybugs (24 h of age). The concentration of nitrogen on grape leaves was measured during both experiments by a SPAD chlorophyll metre, showing statistical differences among treatments. The nitrogen fertilization significantly affected the investigated P. ficus parameters, providing consistent results in both laboratory and screenhouse trials. The vine mealybug females exhibited higher survival and fecundity, larger body size and lower development time on plants supplied with higher nitrogen fertilization rates. Survival, body size and fecundity of P. ficus were positively correlated with the leaf nitrogen concentration, whereas the development time was negatively correlated. Fertility did not vary significantly among treatments. Our results show that high nitrogen regimes increase the reproductive performance of P. ficus on grapevines and point out the importance of implementing balanced fertilization plans in grapevine IPM programs to reduce population densities and prevent insect outbreaks.